2020
DOI: 10.3390/metabo11010006
|View full text |Cite
|
Sign up to set email alerts
|

The Liability Threshold Model for Predicting the Risk of Cardiovascular Disease in Patients with Type 2 Diabetes: A Multi-Cohort Study of Korean Adults

Abstract: Personalized risk prediction for diabetic cardiovascular disease (DCVD) is at the core of precision medicine in type 2 diabetes (T2D). We first identified three marker sets consisting of 15, 47, and 231 tagging single nucleotide polymorphisms (tSNPs) associated with DCVD using a linear mixed model in 2378 T2D patients obtained from four population-based Korean cohorts. Using the genetic variants with even modest effects on phenotypic variance, we observed improved risk stratification accuracy beyond traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Previously, the use of PRS to predict cardiovascular events among T2D patients was not clear. Hong et al (Hong et al, 2020) constructed PRS for CVD on 2,378 T2D patients and explored its prediction performance in the same dataset. One great limitation of this study was the lack of an independent validation dataset for PRS performance analysis, while in our study, we built the subtype PRSs using large-scale GWASs and tested the performance through cross-validation, which was more appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, the use of PRS to predict cardiovascular events among T2D patients was not clear. Hong et al (Hong et al, 2020) constructed PRS for CVD on 2,378 T2D patients and explored its prediction performance in the same dataset. One great limitation of this study was the lack of an independent validation dataset for PRS performance analysis, while in our study, we built the subtype PRSs using large-scale GWASs and tested the performance through cross-validation, which was more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…With much larger studies and improved PRS methods available now, we set out to build a new PRS for CVD onset among T2D patients. Since several studies have shown that utilizing a meta-analytic strategy to build PRS can help better capture the genetic risk information ( Inouye et al, 2018 ); also considering that CAD, IS, and HF are the major subtypes of CVD events with similar clinical implications and management ( Hong et al, 2020 ; Ma et al, 2022 ) and there are strong genetic correlations among these three subtypes to potentially boost power of PRS ( Dichgans et al, 2014 ; Verweij et al, 2017 ; Hong et al, 2020 ; Koyama et al, 2020 ), here we build a new PRS by combining the three “optimal” PRSs trained for each of these three CVD subtypes. With the newly-built meta-PRS CVD , we then comprehensively evaluate its prediction performance for CVD events among T2D patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of such rare, putatively damaging variants in healthy population cohorts 3 can provide a lower boundary for estimates of penetrance, and individuals in both clinical and population cohorts display a spectrum of phenotypic variability caused by similar or identical variants 1,4 . Previous research has suggested that common genetic variants can modify the penetrance or expressivity of phenotypes caused by rare genetic variants [5][6][7] , potentially through the liability threshold model, which posits that a certain threshold of disease susceptibility needs to be crossed before clinically-diagnosable disease manifests [8][9][10][11] . Some damaging rare variants may reach this threshold alone, resulting in a monogenic disease phenotype with 100% penetrance, while other variants may need additional genetic, environmental, or other modifiers to reach this threshold 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested that common genetic variants can modify the penetrance or expressivity of phenotypes caused by rare genetic variants [5][6][7] , potentially through the liability threshold model, which posits that a certain threshold of disease susceptibility needs to be crossed before clinically-diagnosable disease manifests [8][9][10][11] . Some damaging rare variants may reach this threshold alone, resulting in a monogenic disease phenotype with 100% penetrance, while other variants may need additional genetic, environmental, or other modifiers to reach this threshold 8 . In certain diseases, common variant burden has been shown to confer a risk similar to that of a deleterious monogenic variant, where the highest polygenic risk may be equivalent to that conferred by a monogenic variant 12,13 .…”
Section: Introductionmentioning
confidence: 99%